Review—Towards the Two-Dimensional Hexagonal Boron Nitride (2D h-BN) Electrochemical Sensing Platforms. Issue 12 (31st August 2020) - Angizi, Shayan; Khalaj, Maryam; Alem, Sayed Ali Ahmad; Pakdel, Amir; Willander, Magnus; Hatamie, Amir; Simchi, Abdolreza
Abstract : Electrochemical sensing performance of two-dimensional hexagonal boron nitride (2D h-BN) has traditionally been suppressed by their intrinsic electrical insulation and deficient electron transportation mechanism. However, the excellent electrocatalytic activity, high specific surface area, N- and B-active edges, structural defects, adjustable band gap through interaction with other nanomaterials, and chemical functionalization, makes 2D h-BN ideal for many sensing applications. Therefore, finding a pathway to modulate the electronic properties of 2D h-BN while the intrinsic characteristics are well preserved, will evolve a new generation of highly sensitive and selective electrochemical (bio)sensors. That is why extensive research has recently focused on the challenge to functionalize 2D h-BN by controlling the surface chemical reactions with external species, particularly metal nanoparticles. This review summarizes the most recent progress in the application of 2D h-BN nanosheets in electrochemical (bio)sensing. We will explore the fabrication techniques of 2D h-BN for electrochemical applications followed by thorough discussion on their advantages, shortcomings, and promising possibilities as (bio)sensing platforms in near future.